2016
DOI: 10.1002/anie.201605622
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conductance through a Quadruple‐Hydrogen‐Bond‐Bridged Supramolecular Junction

Abstract: A series of self-complementary ureido pyrimidinedione (UPy) derivatives modified with different aurophilic anchoring groups were synthesized. Their electron transport properties through the quadruple hydrogen bonds in apolar solvent were probed employing the scanning tunneling microscopy break junction (STMBJ) technique. The molecule terminated with a thiol shows the optimal electron transport properties, with a statistical conductance value that approaches 10(-3)  G0 . The (1) H NMR spectra and control experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 38 publications
(19 reference statements)
1
36
0
1
Order By: Relevance
“…UPy moieties can form self-complementary dimers via quadruple hydrogen bonding interaction and have been utilized to prepare self-healable polymer gels. [57][58][59][60][61] The feeding ratio of 1IBDP/ 2IBDP, acrylamide, UPy-MA and MBAA is 1 : 100 : 2.5 : 2. The two gels containing 1IBDP and 2IBDP are simplied as g-1IBDP and g-2IBDP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…UPy moieties can form self-complementary dimers via quadruple hydrogen bonding interaction and have been utilized to prepare self-healable polymer gels. [57][58][59][60][61] The feeding ratio of 1IBDP/ 2IBDP, acrylamide, UPy-MA and MBAA is 1 : 100 : 2.5 : 2. The two gels containing 1IBDP and 2IBDP are simplied as g-1IBDP and g-2IBDP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we measure the conductance of amino acids by using an STM break junction [17,22,23,24,25,26,27]. Amino acids with different kinds of anchoring groups, including l -alanine, l -methionine, l -aspartic acid, and l -glutamic acid, were measured and compared.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Hong et al . further investigated the charge transport properties through supramolecular interactions of quadruple hydrogen bonds in ureido pyrimidinedione . These works suggested that the charge transport abilities across supramolecular interaction are quite high and even equal with the covalent interaction in single‐ molecule junctions.…”
Section: Controversies Of the Charge Transport Investigation Of The Pmentioning
confidence: 99%